The genus Litsea in traditional Chinese medicine: An ethnomedical, phytochemical and pharmacological review. (22nd April 2015) - Kong, De-Gang; Zhao, Yu; Li, Guo-Hui; Chen, Bang-Jiao; Wang, Xiao-Ning; Zhou, Hong-Lei; Lou, Hong-Xiang; Ren, Dong-Mei; Shen, Tao
Abstract: Ethnopharmacological relevance: The genus Litsea, mainly distributed in the tropical and subtropical regions, has been used in traditional and indigenous Chinese medicines for the treatment of diarrhea, stomachache, dyspepsia, gastroenteritis, diabetes, edema, cold, arthritis, asthma, pain, traumatic injury, etc. for a long history. The present review aims to provide a comprehensive summary on the ethnomedical uses, phytochemistry, and pharmacology of the Litsea species used in traditional Chinese medicine (TCM). Based on these data, evidences supporting their ethnopharmacological effectiveness are illustrated, and opportunities for the future research and development as well as the therapeutic potential of this genus are analyzed to highlight the gaps in our knowledge that deserves further investigation. Material and methods: Information on the Litsea species was collected via electronic search (using Pubmed, SciFinder, Google Scholar, Web of Science and CNKI) and a library search for articles published in peer-reviewed journals. Furthermore, information was also obtained from some local books on ethnopharmacology. Results: Twenty plants of the genus Litsea are found to be important traditional medicines in China, and have a long medicinal application for diarrhea, stomachache, dyspepsia, gastroenteritis, diabetes, edema, cold, arthritis, asthma, pain, traumatic injury, etc . Over 200 ingredients have been identified from these 20 Litsea species used in TCM, and flavonoids, terpenoids and alkaloids are considered as the characteristic and bioactive constituents. The crude extracts and the isolated metabolites of these medicinal plants have exhibited some in vitro and in vivo pharmacological effects, including antimicrobial, hepatoprotection, anti-inflammatory, antiasthmatic, immunomodulation, anti-diabetic, anticholelithogenic, as well as function on central nervous system, etc . Conclusions: The extensive literature survey reveals Litsea species to be a group of important medicinal plants used for the ethnomedical treatment of gastrointestinal diseases, diabetes, inflammatory disorders, and microbial infection in TCM. Pharmacological investigations have supported the use of some Litsea species in the traditional medicines. In addition, further researches targeting individual ingredients responsible for the pharmacological effects, as well as their mechanisms of action are necessary. The outcome of these studies will further support the therapeutic potential of the genus Litsea, and provide convincing evidences to its future clinical applications in modern medicine. Graphical abstract: